KARATERISTIK DAN MEKANISME PERDAGANGAN CONTRACT FOR DIFFERENCE (CFD) SEBAGAI ALTERNATIF INVESTASI KEUANGAN (Studi Kasus Pada Pasar Derivatif di Australia) - Widiyanti, Novi Wulandari (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2010)
The paper exploresthe nature of CFDs as a derivative and CFDs as hedging instrumentin derivatif markets in Australia. It argues that CFDis leveraged instrument, which means they offer the potential to make a higher return from a smaller initial investment relative to the total position value. Using CFD, we can obtain full exposure to a share or commodity for a fraction of the price of buying the underlying asset. The higher percentage return from the CFD demonstrates how leverage can work. The writer presents two parts in describing CFDâs nature and trading mechanism which are:the nature of the CFDs, which include CFDsâ characteristics and how they are traded. This part will focus on equity CFDs which underlying instrument is stocks. The second part will be an application of delta neutral hedging of long stock position by using and option compare to CFDs. Keywords: derivatif instrument, CFD, underlying asset, hedging, long position, short position